2015
DOI: 10.4236/ojgas.2015.57015
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of the Patients Suffering from Chronic Liver Diseases at the University Health Center Campus of Lome

Abstract: Objective: Assess the quality of life (QOL) of the patients suffering from chronic liver diseases in our service. Patients and Method: A transversal prospective study conducted at the service of hepatology and gastroenterology at the University health center Campus of Lomé from August 1, 2013 to August 31, 2014. We have used the short form 36 health survey questionnaire (SF-36). Patients of cirrhosis and hepatocellular carcinoma admitted during the said period were selected. Patients suffering from any other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
3
1
0
3
Order By: Relevance
“…The three most common etiologic contributors of CLD identified in the present review were HBV, alcohol, and HCV accounting for 40.0% (range: 22.0% to 78.0%), 17.0% (range: 2.0% to 56%), and 15.0% (range: 1.0% to 38.0%), respectively. Consistent with our finding, a study from Togo has reported HBV (66%), alcohol abuse (57%), and HCV (12.3%) as the three principal causes of CLD [ 11 ]. Globally, HBV and HCV are the major cause of CLD [ 6 , 41 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The three most common etiologic contributors of CLD identified in the present review were HBV, alcohol, and HCV accounting for 40.0% (range: 22.0% to 78.0%), 17.0% (range: 2.0% to 56%), and 15.0% (range: 1.0% to 38.0%), respectively. Consistent with our finding, a study from Togo has reported HBV (66%), alcohol abuse (57%), and HCV (12.3%) as the three principal causes of CLD [ 11 ]. Globally, HBV and HCV are the major cause of CLD [ 6 , 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, NAFLD accounted for 25% of the CLD causes globally, with the highest report from western countries (17% to 46%) [ 10 ]. In Africa, a study from Togo has reported HBV (66%), alcohol abuse (57%), and HCV (12.3%) as the most common etiologies of CLD [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Παρόμοια αποτελέσματα βρέθηκαν και στη μελέτη των Bagny και συν, στην οποία συμμετείχαν 114 ασθενείς με ΚΗ (Bagny et al, 2015). Σύμφωνα με αυτή τη μελέτη, αλλά και άλλες παρόμοιες μελέτες, διάφορες παθολογικές καταστάσεις που σχετίζονται με την πρόκληση ΚΗ, όπως οι ηπατίτιδες Β και C και η κατάχρηση αλκοόλ έχουν αξιοσημείωτα αρνητικό αντίκτυπο στην ΠΖ αυτών των ασθενών (Bouglouga et al, 2012;Bagny et al, 2015).…”
Section: επίδραση της εκπαίδευσης στην ποιότητα ζωής ασθενών με κίρρωση ήπατοςunclassified
“…Η δυνατότητα σύνθεσης των αποτελεσμάτων μελετών σχετικά με την ΠΖ των ασθενών με ΚΗ είναι σημαντικά περιορισμένη, δεδομένου ότι προκύπτουν από μια ποικιλία εργαλείων μέτρησης, τα οποία είναι είτε ειδικά για την χρόνια ηπατική νόσο (Sharif et al, 2005;Zandi et al, 2005;Noghabi et al, 2010;Wigg et al, 2013;Taha et al, 2015;Alavinejad et al, 2019), είτε είναι γενικά εργαλεία εκτίμησης της ΠΖ (Foster, Goldin & Thomas, 1998;van der Plas et al, 2003;Bouglouga et al, 2012;Gao et al, 2012;Bagny et al, 2015;Srivastava, 2015;Hjorth et al, 2018;Zhang et al, 2019), είτε είναι συνδυασμός και των δύο (Younossi et al, 2000;Marchesini et al, 2001;Younossi et al, 2001;Häuser, Holtmann & Grandt, 2004). Ως εκ τούτου, πρέπει να λαμβάνεται υπόψιν η ευαισθησία των εργαλείων για την ανίχνευση αλλαγών στην ΠΖ πριν και μετά από την εκπαιδευτική διαδικασία.…”
Section: επίδραση της εκπαίδευσης στην ποιότητα ζωής ασθενών με κίρρωση ήπατοςunclassified
See 1 more Smart Citation